Additions to the cicada fauna of Venezuela with the description of a new species and checklist of the Venezuelan cicada fauna (Hemiptera: Cicadomorpha: Cicadidae) - Sanborn, Allen F. (Zootaxa, 2007)
The new Neotropical cicada species Fidicinoides flavipronotum sp. n. is described. Comparisons are made to other members of the genus found in Venezuela. Fidicina distanti Goding, 1925 is transferred to Fidicinoides Boulard & Martinelli and Diceroprocta bilaqueata (Uhler, 1903) is transferred to Ariasa Distant. Eleven additional species are recorded for the first time from Venezuela increasing the cicada fauna diversity of the country by 31%. A checklist of Venezuelan species is provided.